2021
DOI: 10.1002/pd.6043
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive prenatal test uptake in socioeconomically disadvantaged neighborhoods

Abstract: Objective Non‐Invasive Prenatal Testing (NIPT) is increasingly being implemented worldwide. In public health programs, equitable access to healthcare is a fundamental principle which also applies to fetal aneuploidy screening. However, the out‐of‐pocket costs of NIPT may lead to sociodemographic disparities in uptake of screening. This study assessed whether there is a difference in the uptake of NIPT in socioeconomically disadvantaged neighborhoods compared to all other neighborhoods in the Netherlands, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Our findings on geographic variation are consistent with research from Australia and the Netherlands which found that people living in socioeconomically disadvantaged neighborhoods were less likely to receive NIPT 9,10 . The finding that people with Medicaid coverage were less likely to receive NIPT is inconsistent with a single‐site study in Wisconsin which found that pregnant people with Medicaid were more likely to receive NIPT than those with commercial coverage 6 .…”
Section: Cohort  Nipt Rate Adjusted or (95% Ci) Psupporting
confidence: 70%
“…Our findings on geographic variation are consistent with research from Australia and the Netherlands which found that people living in socioeconomically disadvantaged neighborhoods were less likely to receive NIPT 9,10 . The finding that people with Medicaid coverage were less likely to receive NIPT is inconsistent with a single‐site study in Wisconsin which found that pregnant people with Medicaid were more likely to receive NIPT than those with commercial coverage 6 .…”
Section: Cohort  Nipt Rate Adjusted or (95% Ci) Psupporting
confidence: 70%
“…Such a difference in NIPT uptake was reportedly smaller for the youngest maternal age-group (≤25 years). However, this variation in uptake could create disparities that would undermine the goals of a national fetal aneuploidy screening program [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study found some evidence for the former when it presented vignettes to Dutch citizens and found that respondents agreed less with a pregnant woman declining NIPT when the testing was fully funded [24]. A recent study showing that NIPT uptake in the Netherlands was two times lower in socioeconomically disadvantaged neighborhoods provides strong support for the latter [25]. The out-of-pocket cost for NIPT will disappear in the Netherlands as of April 2023 [26], which will eliminate the barrier to equitable access, but may introduce other concerns such as less informed decisionmaking and routinization.…”
Section: Discussionmentioning
confidence: 99%